Two-dimensional cell membrane chromatography guided screening of myocardial protective compounds from Yindan Xinnaotong soft capsule - Shao, Si-Min; Ji, Xuan; Wang, Xing; Liu, Run-Zhou; Cai, Yu-Ru; Lin, Xiaobing; Zeng, Ze-Jie; Chen, Ling; Yang, Liu; Yang, Hua; Gao, Wen (Chinese medicine, 2025)
Cell membrane chromatography (CMC) is a biochromatography with a dual function of recognition and separation, offering a distinct advantage in screening bioactive compounds from Chinese medicines (CMs). Yindan Xinnaotong soft capsule (YD), a CM formulation, has been widely utilized in the treatment of cardiovascular disease. However, a comprehensive mapping of the myocardial protective active compounds remains elusive. To establish a stable and efficient 2D H9c2/CMC-RPLC-MS system, and to utilize it for screening the active compounds of YD that are associated with myocardial protection. An imidazole-modified silica gel exhibiting high modification efficiency and protein binding capacity was synthesized to enhance the longevity and efficiency of H9c2/CMC. Subsequently, the potentially bioactive compounds of YD were screened by integrating the 2D H9c2/CMC-RPLC-MS system with a high-content component knockout strategy. Additionally, an RNA-seq approach was employed to predict the targets and mechanisms of YD and the active compounds for myocardial protection. The developed imidazole-modified H9c2/CMC exhibits remarkable selectivity, specificity, stability, and reproducibility. Following three rounds of screening, a total of 24 potential myocardial protective compounds were identified, comprising 8 flavonoids, 8 phenolic acids, 4 saponins, and 4 tanshinones. Bioinformatic analysis utilizing RNA-seq indicated that the FOXO signaling pathway, with FOXO3 identified as a key target, plays a significant role in the cardioprotective effects of YD. Furthermore, all 24 screened compounds exhibit strong binding affinities with FOXO3 evaluated by molecular docking. A highly stable and efficient 2D imidazole-modified H9c2/CMC-RPLC-MS system was developed, allowing for the screening of potentially active compounds from YD. Through the integration of the bioinformatic analysis, the pharmacodynamic foundation of YD for myocardial protection has been comprehensively characterized.